The path towards a truly holistic and comprehensive development of the individual, the society and the nation in this age of turbulence - Hassan, Mohd. Kamal (2011)
Introduction Looking at the state of the world and the environment today, we recall what Alan Greenspan, the former Chairman of the Federal Reserve Board of U.S.A. wrote in 2007, namely The Age of Turbulence: Adventures in a New World (Penguin Books 2007). Although his focus was on the financial tumult of recent times, particularly in the U.S.A., the title of his work is an apt description of the current state of economic and financial turmoil, the political uncertainties, social upheavals, moral degeneration and potential environmental catastrophes. In view of these highly challenging global scenarios, a fundamental review of the well-established conventional systems have to be undertaken by Muslim leaders, intellectuals and scholars if the Muslim world and communities are not to remain hostage to the provenly corrupt and unreliable internal and external structures.